Pemetaan Kecepatan Gelombang Geser Hingga Kedalaman 30 Meter di Wilayah Jakarta Selatan Menggunakan Inversi Eliptisitas Rayleigh - Bambang Sunardi; Dwi Budi Susanti; Nana Dyana; Amirul Fitria Adila; Wuri Handayani (Jurnal Stasiun Geofisika Sleman, 2023)
Recent research has revealed that there is a potential for large earthquakes in the southern area of Jakarta due to the Baribis fault which extends from Purwakarta, Karawang, Bekasi, south of Jakarta, Tangerang, to Banten. The fault is most likely active, with the western part still locked. This locked section makes Jakarta and its surroundings vulnerable to major earthquakes in the future. The purpose of this study was to map the average shear wave velocity to a depth of 30 m (Vs30) in the South Jakarta area using the Rayleigh wave ellipticity inversion method. The microtremor data used were 15 points around the South Jakarta area. Microtremor data were analyzed using the HVTFA method from Geopsy, and inversion was performed to obtain a shear wave velocity (Vs) profile for each measurement point. Furthermore, the value of Vs30 is calculated based on the formula in SNI 1726:2019. The results showed that the value of Vs30 varied from 190–350 m/s. The Vs30 mapping shows that the northern part of Pesanggrahan and Kebayoran Lama Districts has a higher Vs30 value. Detailed soil condition maps based on the Vs30 distribution are very important not only for urban settlements but also for site selection and site safety evaluation studies